"Squalenoylcurcumin" Nanoassemblies as Water‐Dispersible Drug Candidates with Antileishmanial Activity. Issue 2 (18th December 2014) - Cheikh‐Ali, Zakaria; Caron, Joachim; Cojean, Sandrine; Bories, Christian; Couvreur, Patrick; Loiseau, Philippe M.; Desmaële, Didier; Poupon, Erwan; Champy, Pierre
Abstract Curcumin, a natural polyphenolic compound, showed antiparasitic potential, including trypanocidal and leishmanicidal activity, in several in vitro and in vivo models. The molecule is well tolerated in humans. However, it is insoluble in water and displays poor oral bioavailability as a result of low absorption. New derivatives of curcumin were prepared by esterification of one or two of its phenolic groups with 1, 1′, 2‐tris‐norsqualenic acid. These "squalenoylcurcumins" were formulated as water‐dispersible nanoassemblies of homogeneous size, and they proved to be stable. Squalenoylcurcumins were inactive against Trypanosoma brucei brucei trypomastigotes, even as nanoassemblies, in contrast with curcumin. However, against Leishmania donovani promastigotes, the activities of the squalenoylcurcumins and their nanoassemblies were enhanced relative to that of curcumin. In L. donovani axenic and intramacrophagic amastigotes, they showed activity in the range of miltefosine, with good selectivity indexes. In regard to their dispersibility in water and to the safety of curcumin, these nanoassemblies are promising candidates for preclinical study toward the treatment of visceral leishmaniasis.